Atypical resting state neuromagnetic connectivity and spectral power in very preterm children. (25th February 2019) - Kozhemiako, Nataliia; Nunes, Adonay; Vakorin, Vasily A.; Chau, Cecil M. Y.; Moiseev, Alexander; Ribary, Urs; Grunau, Ruth E.; Doesburg, Sam M.
Abstract : Background: Children born very preterm often display selective cognitive difficulties at school age even in the absence of major brain injury. Alterations in neurophysiological activity underpinning such difficulties, as well as their relation to specific aspects of adverse neonatal experience, remain poorly understood. In the present study, we examined interregional connectivity and spectral power in very preterm children at school age, and their relationship with clinical neonatal variables and long‐term outcomes (IQ, executive functions, externalizing/internalizing behavior, visual‐motor integration). Methods: We collected resting state magnetoencephalographic (MEG) and psychometric data from a cohort at the age of 8 years followed prospectively since birth, which included three groups: Extremely Low Gestational Age (ELGA, 24–28 weeks GA n  = 24, age 7.7 ± 0.38, 10 girls), Very Low Gestational Age (VLGA, 29–32 weeks GA n  = 37, age 7.7 ± 0.39, 24 girls), and full‐term children (38–41 weeks GA n  = 39, age 7.9 ± 1.02, 24 girls). Interregional phase synchrony and spectral power were tested for group differences, and associations with neonatal and outcome variables were examined using mean‐centered and behavioral Partial Least Squares (PLS) analyses, respectively. Results: We found greater connectivity in the theta band in the ELGA group compared to VLGA and full‐term groups, primarily involving frontal connections. Spectral power analysis demonstrated overall lower power in the ELGA and VLGA compared to full‐term group. PLS indicated strong associations between neurophysiological connectivity at school age, adverse neonatal experience and cognitive performance, and behavior. Resting spectral power was associated only with behavioral scores. Conclusions: Our findings indicate significant atypicalities of neuromagnetic brain activity and connectivity in very preterm children at school age, with alterations in connectivity mainly observed only in the ELGA group. We demonstrate a significant relationship between connectivity, adverse neonatal experience, and long‐term outcome, indicating that the disruption of developing neurophysiological networks may mediate relationships between neonatal events and cognitive and behavioral difficulties at school age.